DECENTRALIZED WASTEWATER TREATMENT AND ENERGY RECOVERY IN URBAN SETTINGS: PERFORMANCE OF A MODIFIED SEPTIC TANK-MICROBIAL FUEL CELL SYSTEM - Dyanung Larasati; Ahmad Soleh Setiyawan; Nawatch Surinkul; Vandith Va (Universitas Trisakti, 2025)
Microbial Fuel Cell (MFC) technology has attracted interest for its dual role in wastewater treatment and energy generation. Aim: This study aimed to evaluate the performance of a Modified Septic Tank-Microbial Fuel Cell (MST-MFC) for office domestic wastewater treatment, focusing on organic matter, ammonia removal, and electricity generation. Methodology and results: In this study, synthetic wastewater was prepared to simulate the typical composition of domestic effluent from office buildings. The main variables measured in this study included pH, temperature, Chemical Oxygen Demand (COD), Dissolved Oxygen (DO), and ammonia levels. A 196 L reactor (36 h HRT) with anoxic, anaerobic, aerobic, and sedimentation zones was equipped with three pairs of zinc–copper electrodes (2 cm spacing) placed in anaerobic (anode) and aerobic (cathode) chambers. Synthetic wastewater with controlled COD:N:P ratios was applied at two organic loading rates (OLRs): 7 and 11.94 mg COD/L.h. At the lower OLR, COD removal reached 100% versus 93.85% at the higher OLR. Ammonia removal was also higher (27.61% vs. 17.59%), while electricity generation peaked with 461.88 mV, 355.67 mW/m2, and 0.0970% Coulombic efficiency. Conclusion, significance and impact study: The MST-MFC showed strong potential for decentralized wastewater treatment with energy recovery, though limited ammonia removal indicates further optimization is needed, with OLR as a key factor.